Functionalising insoluble pea protein aggregates using high-pressure homogenisation: Effects on physicochemical, microstructural and functional properties. (October 2022) - Ong, Kian Siang; Chiang, Jie Hong; Sim, Shaun Yong Jie; Liebl, David; Madathummal, Mufeeda; Henry, Christiani Jeyakumar
Abstract: Commercial plant protein isolates contain a large fraction of non-functional proteins due to the harsh processing conditions used. Therefore, greater value can be unlocked by functionalising these "inert" plant proteins. Using commercial insoluble pea protein isolate (I-PPI) as an example, this study demonstrates the application of high-pressure homogenisation (HPH) as a physical method to improve the techno-functionality of I-PPI. The dispersions were HPH-treated at 60, 120, or 180 MPa for one, three, and five pressure cycles. HPH treatments resulted in decreased particle size (from 16.7 ± 1.3–9.4 ± 0.2 µm at 60 MPa) and increased zeta-potential. Microstructural observations revealed the formation of smaller aggregate clusters and flake-like structures after HPH treatments. The protein solubility of I-PPI (15.9 ± 2.0 %) under acidic conditions (pH 2) significantly increased at all HPH treatment levels, with the greatest increase at 120 MPa for 5 passes (27.2 ± 2.0 %). Remarkably, the non-gelling I-PPI was able to form self-standing gels (15 % w/w) after HPH treatments, with the greatest gel strength observed at 180 MPa. The emulsifying and foaming stability of HPH-treated I-PPI increased from 60 to 120 MPa but decreased at 180 MPa. Overall, our results demonstrate a key paradigm in protein modification: transforming insoluble plant proteins into functional protein ingredients. Graphical Abstract: ga1 Highlights: High-pressure homogenisation (HPH) to improve the functionality of plant proteins. HPH treatments decreased particle size and increased zeta-potential. Formation of aggregate clusters and flake-like structures after HPH treatments. Solubility at acidic pH significantly increased at all HPH treatments. The greatest gel strength was observed for HPH treatments at 180 MPa.